The best mistake ever! and other stories - Scarry, Richard (New York : Random House, 1984)
Three stories about Lowly Worm and his friends include The best mistake ever, A visit to Mr. Fixit, and Best friends.
310
Keywords: Children's stories, American; Animals -- Fiction; Short stories